Designing of casual wear for wheelchair users - Natalija Sadretdinova; Sergij Bereznenko; Larysa Bilotska; Halina Szafrańska; Maria Pawlowa (Communications in Development and Assembling of Textile Products, 2022)
Functionality and comfort are important requirements for adaptive clothing. To ensure the compliance of clothing with these requirements, it is necessary to take into account, on the one hand, consumer conditions, on the other hand specific needs driven from social and psychophysiological adaptation to the living conditions. Thus, for people who are restricted to the sitting position for their entire life due to their disabilities, it is important to avoid skin diseases that occur in conditions of constant contact of the skin with hard surfaces under pressure. Therefore, the aim of our work was to improve functional clothing for disabled people based on the analysis of ergonomics and consumer requirements through the application of new technologies.